Efisiensi Algoritma dan Notasi O-Besar - Subandijo, Subandijo (Bina Nusantara University, 2011)
Efficiency or the running time of an algorithm is usually calculated with time complexity or space complexity as a function of various inputs. It is common to estimate their complexity in the asymptotic sense, i.e., to estimate the complexity function for arbitrarily large input. Brute-force algorithm is the easiest way to calculate the performance of the algorithm. However, it is not recommended since it does not sufficiently explain the efficiency of the algorithm. Asymptotic estimaties are used because different implementations of the same algorithm may differ in efficiency. The big-O notation is used to generate the estimation.